Intestinal Villous M Cells: An Antigen Entry Site in the Mucosal Epithelium - Jang, Myoung Ho; Kweon, Mi-Na; Iwatani, Koichi; Yamamoto, Masafumi; Terahara, Kazutaka; Sasakawa, Chihiro; Suzuki, Toshihiko; Nochi, Tomonori; Yokota, Yoshifumi; Rennert, Paul D.; Hiroi, Takachika; Tamagawa, Hiroshi; et al. (Proceedings of the National Academy of Sciences - PNAS, 2004)
M cells located in the follicle-associated epithelium of Peyer's patches (PP) are shown to be the principal sites for the sampling of gut luminal antigens. Thus, PP have long been considered the gatekeepers of the mucosal immune system. Here, we report a distinct gateway for the uptake of gut bacteria: clusters of non-follicle-associated epithelium-associated Ulex europaeus agglutinin ( UEA)-1+ cells, which we have designated intestinal villous M cells. Interestingly, villous M cells are developed in various PP [or gut-associated lymphoid tissue (GALT)]. null mice, such as in utero lymphotoxin β receptor (LTβR)-Ig-treated, lymphotoxin α ( LTα)-/-, tumor necrosis factor/ LTα -/-, and inhibition of differentiation 2( Id2)-/- mice. Intestinal villous M cells have been observed to take up GFP-expressing Salmonella, Yersinia, and Escherichia coli-expressing invasin, as well as gut bacterial antigen for subsequent induction of antigen-specific immune responses. Thus, the identified villous M cells could be an alternative and PP-independent gateway for the induction of antigen-specific immune responses by means of the mucosal compartment.